RJFA 2019
DOI: 10.7176/rjfa/10-5-03
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Financial Performance of Insurance Industry in Pakistan

Abstract: This study investigated the indicators of financial performance of insurance companies of Pakistan. Gross written premium (GWP), Claim (CLM), Reinsurance (Rei), Management expenditure (MGE), Interest rate (IR), Size (SIZ), Leverage (LEV), Real GDP (RGDP) were taken as factors (independent variables), whereas Sales Profitability (SAP), Investment Income (INP), and Underwriting profit (UWP) were taken as proxy of financial performance. Data of five 5 insurance companies are chosen covering the period of 2013-201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…It indicates that gross domestic product has a positive impact on return on equity. This finding is also similar to the findings of Shawar & Siddiqui (2019). Likewise, the beta coefficients for money supply are negative with return on equity.…”
Section: Regression Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…It indicates that gross domestic product has a positive impact on return on equity. This finding is also similar to the findings of Shawar & Siddiqui (2019). Likewise, the beta coefficients for money supply are negative with return on equity.…”
Section: Regression Analysissupporting
confidence: 88%
“…Similarly, Hasan et al (2018) concluded that the macroeconomic variables (GDP growth rate) have statistically positive significant influence on the performance of non-life insurance companies. Furthermore, Shawar & Siddiqui (2019) found that the gross domestic product have an insignificant but positive relationship with profitability of the insurance industry. In additional, Meher & Zewudu (2020) found that there is the positive relationship between the gross domestic product and profitability of the insurance company.…”
Section: Gross Domestic Productmentioning
confidence: 99%
“…These predictions, however, are referred to as "technical models" in the insurance industry, as they do not take into account other external factors including inflation, regulatory constraints, and practices followed to insure customer retention. Factors such as expenses, investments, reinsurance, and other model adjustments and regulatory constraints assist in arriving at the final premium amount Tsvetkova et al (2021); Shawar and Siddiqui (2019). Developing the best possible "technical models" is essential for an insurance company to enable the prediction of appropriate insurance premiums Guelman (2012), and this is the focus of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…The sustainability and profitability of insurers is vital given the benefits they provide to society and the nation. A well-developed insurance sector reinforces the country's economic system by mitigating the growing financial crisis (Shawar and Siddiqui, 2019).…”
Section: Introductionmentioning
confidence: 99%